THE FIRST JOINT CONFERENCE OF THE INTERNATIONAL SOCIETY OF HYPERTENSION (ISH) AND RUSSIAN SOCIETY OF HYPERTENSION (RSH), OCTOBER 27,2018, MOSCOW, RUSSIA - article Editorial (Евразийский Кардиологический Журнал)
.